2013
DOI: 10.1051/epjap/2012120207
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of the structural and electronic properties of Mg3Bi2in hexagonal and cubic phases

Abstract: We study the structural and electronic properties of Mg3Bi2 in both hexagonal and body center cubic (bcc) phases by using first-principles calculations based on the density functional theory (DFT). We solve the Kohn-Sham equations using the full potential linearized augmented plane wave (FP-LAPW) method. The generalized gradient approximations as proposed by Perdew-Burke-Ernzerhof (PBE sol GGA) and Engel-Vosko (EV-GGA) are employed to calculate the exchange correlation potential. Using GGA, we compute the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
2
9
0
1
Order By: Relevance
“…Zhou et al [15] have found the cohesive energy 2575.36 kJ/mol from rst principle calculations. The calculated lattice parameters at room temperature are in fairly good agreement with available theoretical and experimental data [10,15,16,18,2224]. All values of lattice parameters are given in Table II.…”
Section: Lattice Parameters Density and Thermal Expansionsupporting
confidence: 80%
See 4 more Smart Citations
“…Zhou et al [15] have found the cohesive energy 2575.36 kJ/mol from rst principle calculations. The calculated lattice parameters at room temperature are in fairly good agreement with available theoretical and experimental data [10,15,16,18,2224]. All values of lattice parameters are given in Table II.…”
Section: Lattice Parameters Density and Thermal Expansionsupporting
confidence: 80%
“…Lattice parameters are calculated as a = 4.61 Å and c = 7.24 Å and compared with a considerable amount of experimental and rst principle data [10,15,16,18,2224] which are in agreement with these results (Table II). As the temperature increases from room temperature to 1600 K, constant stress method of Parrinello and Rahman dynamics is used where lattice parameters change in each dimension so that lattice constant a 1 and a 2 diverge from each other and angles do not maintain their α = 90…”
Section: Elastic Constants Bulk Modulus and Shear Modulussupporting
confidence: 55%
See 3 more Smart Citations